Effect of Eye Patching in Rehabilitation of Hemispatial Neglect - Smania, Nicola; Fonte, Cristina; Picelli, Alessandro; Gandolfi, Marialuisa; Varalta, Valentina (Frontiers in Human Neuroscience, 2013)
Eye patching (monocular or right hemifield) has been proposed to improve visuospatial attention to the ignored field in patients with neglect. The aim of this paper is to review the literature on the effects of eye patching in hemispatial neglect after stroke in order to convey evidence-based recommendations to clinicians in stroke rehabilitation. Thirteen intervention studies were selected from the Medline, EMBASE, Scopus, Cochrane Library, CINAHL, PsychINFO, EBRSR and Health Star databases. Methodological quality was defined according to the Physiotherapy Evidence Database. Overall, seven studies used monocular eye patching, five used right hemifield patching and one compared right monocular with right hemifield patching. Seven studies compared normal viewing to monocular or hemifield patching conditions. Six studies included a period of treatment. Three studies included follow-up evaluations. As to the monocular eye patching, four studies reported positive effects of right monocular patching. One study showed an improvement in hemispatial neglect with left monocular patching. Two studies found no superiority of right versus left monocular patching. One study found no effects of right monocular patching. As to the right hemifield eye patching, one study showed improvements in neglect after right hemifield patching. Three studies found that right hemifield patching combined with another rehabilitation technique was more effective than that treatment alone. One study found no differences between right hemifield patching combined with another treatment and that treatment alone. One study found the same effect between right hemifield patching alone and another rehabilitation technique. Our results globally tend to support the usefulness of right hemifield eye patching in clinical practice. In order to define a level of evidence with the standard rehabilitation evidence rating tools, further properly powered randomized controlled trials or meta-analysis are needed.